2001
DOI: 10.1021/la001774w
|View full text |Cite
|
Sign up to set email alerts
|

Selective Exchange and Fixation of Strontium Ions with Ultrafine Na-4-mica

Abstract: A simple preparation process of Na-4-mica (ideal brittle mica composition of Na4Mg6Al4Si4O20F4‚xH2O) from kaolinite yielded a nearly pure and very fine Na-4-mica with a crystallite size of about 0.2 µm. Strontium-sodium ion exchange in the hydrated interlayers of the Na-4-mica was demonstrated with this fine mica. The forward ion exchange of Sr 2+ f 2Na + (Sr-ion adsorption) was determined after equilibration for 4 weeks, and the Sr exchange capacity reached a value of about 200 mequiv (100 g) -1 . The parabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 29 publications
3
68
0
Order By: Relevance
“…Four kinetics models were used to analyse the kinetic data of MB and CR photocatalytic degradation on TiO 2 [20][21][22][23] :…”
Section: The Degradation Kinetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four kinetics models were used to analyse the kinetic data of MB and CR photocatalytic degradation on TiO 2 [20][21][22][23] :…”
Section: The Degradation Kinetic Modelsmentioning
confidence: 99%
“…A small band around 600 nm wavelength for both case of TiO 2 (P25) and synthesized TiO 2 was observed because two aromatic rings in MB starts to degrade creating a mono substituted molecule. This indicates that the photodegradation not only destroys the conjugate system (including −N=N−) but also breaks down partially or totally the intermediate products [19][20][21][22][23][24][25]. Comparing the two dyes, it is observed that chemical structure of MB lends itself more to oxidation by hydroxyl radicals, than does CR.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…It was suggested that the release of guest anion from the nanocomposite could be best described either by dissolution of LDH [18,19] or by diffusion through the LDH [20,21]. The methods used are zeroth order (Equation (1)) [22], first order (Equation (2)) [23], pseudosecond order (Equation (3)) [24] and parabolic diffusion (Equation (4)) [21], for which the equations are given below.…”
Section: Kinetic Studymentioning
confidence: 99%
“…The methods used are zeroth order (Equation (1)) [22], first order (Equation (2)) [23], pseudosecond order (Equation (3)) [24] and parabolic diffusion (Equation (4)) [21], for which the equations are given below. The x is the percentage release of herbicides anion at time t, M i and M f are the initial and final concentrations of herbicides anions, respectively and C is a constant.…”
Section: Kinetic Studymentioning
confidence: 99%
“…Four dissolution-diffusion kinetic models were used to fit the in vitro VP16-LDH release profiles. [36][37][38][39][40] The zero-order model:…”
Section: In Vitro Vp16 Release Test From Vp16-ldhmentioning
confidence: 99%